Implementation of ICT-Based Teacher Administration System to Improve Teaching and Learning Activities - Andri Sutrisno; Muhammad Masruri Dalail; Izzat Amini (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
One of the educational goals is the implementation of teaching and learning activities well in the boarding school environment. For this reason, it is necessary to carry out Information and Communication Technology (ICT) based documentation so that it can be enjoyed together and evaluated the performance of the teachers' service at TMI Al-Amien Prenduan. As for the existence of an ICT-based teacher administration system, it is actually a form of consensus between the caregiver and several teachers in improving the skills of teachers in the field of technology and online-based information. Given the increasingly massive technological developments in contemporary times. This research is included in qualitative field research with a case study research approach. The data collection techniques used are observation, interviews and documentation. While the data analysis techniques used are data reduction, data presentation and data verification. This research results in the implementation of an ICT-based teacher administration system in the field of curriculum, teacher self- development and examination results of the students. While the positive impact of SAG-TMI is the cooperation between the principal and the teachers for the achievement of good teaching and learning process activities so that it can be seen directly by the guardians of the students' academic achievements in the pesantren through ICT-based SAG-TMI.